HISTORIA DE UNA CARTA Y DE SU LECTURA - Cunchillos Ilarri, José Luis; Vita Barra, Juan Pablo (Antigüedad y Cristianismo, 1995)
The authors cover the history of the investigation of queen Puduhepa’s letter, an important historical document found at Ras-ShamraKJgarit (Syna), and written c. 1218 B.C. in Ugaritic. The knowledge of the text itself is stressed as the base for undertaking a historical interpretation: the study of the text in its original language, epigraphic problems, philological analysis, stnictural literary analysis, knowledge of the historical context, assessment of the intellectual and professional capability of the ancient scribe. Moreover, the authors set forth the advantages for the epistolary genre for the understanding of an ancient language like Ugaritic. (...)